Using Vignettes to Explore Caste Attitudes in Central Nepal (HIMALAYA, 2022)
This study aims to explore the attitudes of young persons in Nepal toward caste using completed short stories, or ‘vignettes’, that imagine situations involving intercaste couples. A total of around 230 stories were gathered from 2018 to 2019. The study, conducted among Class 11 and 12 students in around a dozen schools in central Nepal, covered a mixture of rural and urban locations. The results were analyzed quantitatively and qualitatively. The quantitative analysis used simple statistical techniques (p values) to test whether there were statistically significant differences in story outcomes based on author and story characteristics. The analysis suggests, tentatively, that young people do not see caste as a barrier to relationships. The qualitative analysis of tropes and themes illuminated new framings of caste that are now prominent, including narratives that may reflect social change that occurred in the civil war period, and in the rise of identities focused on ‘merit’ and ‘achievement’ in the sphere of work rather than on ascriptive identities like caste and ethnicity.